2010
DOI: 10.1099/mic.0.037309-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spontaneous mutations in PipX functions and regulatory complexes on the cyanobacterium Synechococcus elongatus strain PCC 7942

Abstract: In Synechococcus elongatus sp. PCC 7942, PipX forms complexes with P II , a protein found in all three domains of life as an integrator of signals of the nitrogen and carbon balance, and with the cyanobacterial nitrogen regulator NtcA. We recently showed that previous inactivation of pipX facilitates subsequent inactivation of the glnB gene. Here, we show that the three spontaneous pipX point mutations pipX-92delT, pipX160C.T and pipX194T.A, initially found in different glnB strains, are indeed suppressor muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 36 publications
(36 reference statements)
1
65
0
Order By: Relevance
“…Importantly, Western blots showed that individual inactivation of pipX or pipY decreased the levels of PipY or PipX by 15-fold or 2-fold, respectively ( Figure 2 and Table 2 ), suggesting that the protein levels of PipY are highly dependent on pipX gene or gene product(s). In line with this, expression from the strong CK1 promoter (strain CK1X), resulting in a significant increase in the levels of PipX (Espinosa et al, 2010), produced a 3.4-fold and 4.3-fold increase in PipX and PipY, respectively ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 55%
“…Importantly, Western blots showed that individual inactivation of pipX or pipY decreased the levels of PipY or PipX by 15-fold or 2-fold, respectively ( Figure 2 and Table 2 ), suggesting that the protein levels of PipY are highly dependent on pipX gene or gene product(s). In line with this, expression from the strong CK1 promoter (strain CK1X), resulting in a significant increase in the levels of PipX (Espinosa et al, 2010), produced a 3.4-fold and 4.3-fold increase in PipX and PipY, respectively ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 55%
“…In some cases, inactivation of essential genes may be facilitated by suppressor mutations, as it is the case with glnB in S. elongatus , which can be readily inactivated in the presence of loss-of-function mutations at pipX (Espinosa et al, 2009, 2010). However, attempts to obtain S. elongatus plmA null strains in different mutant backgrounds have so far been unsuccessful (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Under these nitrogen regimes, particularly in ammonium, the concentration of 2-OG is expected to be relatively low and transcriptional regulation by NtcA-PipX complexes would not have widespread importance in WT cells. Because the pipX Y32A or pipX E4A allele is associated with a resistance marker (C.S3 cassette) that decreases pipX gene expression (18), a WT derivative with the same insertion in the identical position (strain CS3X) was required to perform isogenic mutant/control comparisons. Therefore, two strains were used as WT controls: WT S. elongatus for mutant strain SA591, which carries the ΔpipX allele, and CS3X for strains CS3X E4A and CS3X…”
Section: Resultsmentioning
confidence: 99%